PENGARUH HARGA, PROMOSI, DAN KEMUDAHAN AKSES TERHADAP KEPUTUSAN PEMBELIAN “STUDI PADA UMKM KULINER ANGKRINGAN MAS GUN SEMARANG SELATAN - Dian Rizky Febriana (CV. Denasya Smart Publisher, 2026)
The rapid growth of the culinary industry, particularly in the MSME sector, has intensified competition, requiring business actors to understand factors influencing consumer purchasing decisions. Price, promotion, and ease of access are key variables shaping consumers’ perceived value. This study aims to analyze the effects of price, promotion, and ease of access on purchasing decisions at the culinary MSME Angkringan Mas Gun in South Semarang. A quantitative approach was applied using a survey of 385 respondents determined through the Lemeshow formula. Data were collected using Likert-scale questionnaires and analyzed with SPSS, including validity, reliability, classical assumption tests, and hypothesis testing using t-tests and F-tests. The partial t-test results indicate that price has a positive and significant effect on purchasing decisions (β = 0.402; p = 0.000), promotion also shows a positive and significant effect (β = 0.232; p = 0.000), and ease of access has a positive and significant effect (β = 0.331; p = 0.000). Simultaneously, all three variables have a positive and significant influence on consumer purchasing decisions. The study concludes that affordable pricing, effective promotional strategies, and easily accessible locations enhance consumers’ purchasing decisions. These findings provide practical insights for culinary MSMEs in developing competitive and sustainable marketing strategies.